Stainless steel bars and electromagnetic parts

The optimized stainless steel composition addresses the limitations of existing electromagnetic stainless steel by enhancing soft magnetic and cutting properties through controlled nitride particle diameter and solid-soluble content, achieving high-speed cold forging and cutting capabilities.

JP7623400B2Active Publication Date: 2025-01-28NIPPON STEEL CORPORATION
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022563763
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-19
Filing Date
2021-11-16
Publication Date
2025-01-28
Estimated Expiration
2041-11-16

AI Technical Summary

Technical Problem

Existing electromagnetic stainless steel products, such as injectors and electromagnetic valves, face challenges in achieving high-precision and high-output performance due to insufficient soft magnetic characteristics and limitations in high-speed cold forging and cutting properties, which restrict their applications.

Method used

A stainless steel composition with controlled nitride particle diameter and solid-soluble content, optimized through specific chemical elements and processing conditions, including controlled nitride particle diameter of 10 μm or less and solid-soluble N and B amounts of 0.020% or less, enhances soft magnetic and cutting properties.

Benefits of technology

The optimized stainless steel exhibits a compression rate of 70%, crack-free strain speed of 0.1/s or more, and tool life of 50 mm or more, with magnetic force of 5.0A/m or less, enabling high-speed cold forging and cutting properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623400000001
    Figure 0007623400000001
  • Figure 0007623400000002
    Figure 0007623400000002
  • Figure 0007623400000003
    Figure 0007623400000003
Patent Text Reader

Abstract

A stainless steel bar material which has a chemical composition that contains, in mass%, from 0.001% to 0.030% of C, from 0.01% to 4.00% of Si, from 0.01% to 2.00% of Mn, from 0.01% to 4.00% of Ni, from 8.0% to 35.0% of Cr, from 0.01% to 5.00% of Mo, from 0.01% to 2.00% of Cu, from 0.001% to 0.030% of N, 7.000% or less of Al, from 0% to 2.00% of Ti, from 0% to 2.00% of Nb and from 0% to 0.1% of B, with the balance being made up of Fe and impurities. With respect to this stainless steel bar material, the chemical composition additionally contains, in mass%, one or more elements selected from among 0.001% or more of Ti, 0.001% or more of Nb and 0.0001% or more of B; the average particle diameter of nitrides is 10 μm or less; and the amount of N solid-solved in the steel is 0.020% by mass or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to electromagnetic stainless steel, in particular to a stainless steel bar material having excellent high-speed cold forgeability, machinability and soft magnetic properties, and to an electromagnetic part using the same. [Background technology]

[0002] Conventionally, electromagnetic stainless steel products, such as injectors and solenoid valves, have been manufactured by processing, molding, and heat treatment using ferritic stainless steel wires and steel wires, such as SUS430 and SUS410L. However, the soft magnetic properties of stainless steel products manufactured from the above-mentioned ferritic stainless steel wires are not sufficient for high-precision and high-output parts. In addition, these products have the disadvantage that their cold forgeability and machinability cannot meet the high production requirements for parts manufacturing, limiting their applications. In response to the above issues, techniques for optimizing alloy elements have been considered to improve soft magnetic properties, cold forgeability, and machinability (for example, Patent Documents 1 to 3). However, there has been no invention that focuses on the fact that the soft magnetic properties, high-speed cold forgeability, and machinability of ferritic stainless steel rods and wires can be improved by utilizing structure control through a combination of components and processes. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-49606 [Patent Document 2] Japanese Patent Application Publication No. 6-49605 [Patent Document 3] Japanese Patent Application Publication No. 3-44448 Summary of the Invention [Problem to be solved by the invention]

[0004] In view of the above, an object of the present invention is to solve the above problems and provide an electromagnetic stainless steel, in particular a stainless steel bar, which has excellent high-speed cold forgeability, machinability and soft magnetic properties, and an electromagnetic part using the same. [Means for solving the problem]

[0005] The present invention has been made to solve the above-mentioned problems, and provides the following stainless steel bar and electromagnetic component. [1] Chemical composition, by mass%, C:0.001~0.030%, Si:0.01~4.00%, Mn:0.01~2.00%, Ni:0.01~4.00%, Cr:8.0~ Contains 35.0%, Mo: 0.01~5.00%, Cu: 0.01~2.00%, N: 0.001~0.030%, Al: 7.000% or less, moreover, Ti: 0-2.00%, Nb: 0-2.00%, B: 0-0.1000%; Contains one or more selected from Ti: 0.001% or more, Nb: 0.001% or more, and B: 0.0001% or more; Sn:0~2.50%, V:0~2.0%, W:0~3.00%, Ga:0~0.05%, Co:0~2.50%, Sb:0~2.50%, Ta:0~2.50%, Ca:0~0.05%, Mg:0~0.01 2%, Zr: 0~0.012%, REM: 0~0.05%, Pb: 0~0.30%, Se: 0~0.80%, Te: 0~0.30%, Bi: 0~0.50%, S: 0~0.50%, P: 0~0.30%, The balance is Fe and impurities. A stainless steel bar having an average nitride particle size of 10 μm or less and a solute N content of 0.020 mass % or less.

[0006] [2] Chemical composition, in mass%, C:0.001~0.030%, Si:0.01~4.00%, Mn:0.01~2.00%, Ni:0.01~4.00%, Cr:8.0~ Contains 35.0%, Mo: 0.01~5.00%, Cu: 0.01~2.00%, N: 0.001~0.030%, Al: 7.000% or less, moreover, Ti: 0-2.00%, Nb: 0-2.00%, B: 0-0.1000%; Contains one or more selected from Ti: 0.001% or more, Nb: 0.001% or more, and B: 0.0001% or more; Sn:0~2.50%, V:0~2.0%, W:0~3.00%, Ga:0~0.05%, Co:0~2.50%, Sb:0~2.50%, Ta:0~2.50%, Ca:0~0.05%, Mg:0~0.01 2%, Zr: 0~0.012%, REM: 0~0.05%, Pb: 0~0.30%, Se: 0~0.80%, Te: 0~0.30%, Bi: 0~0.50%, S: 0~0.50%, P: 0~0.30%, The balance is Fe and impurities. A stainless steel bar having an average nitride particle size of 10 μm or less and a solute B content of 0.015 mass % or less.

[0007] [3] The stainless steel bar according to [1] or [2], wherein the chemical composition further contains, in mass %, one or more elements selected from the following first to third groups: Group 1 One or more selected from Sn: 0.0001-2.5%, V: 0.001-2.0%, W: 0.05-3.0%, Ga: 0.0004-0.05%, Co: 0.05-2.5%, Sb: 0.01-2.5%, and Ta: 0.01-2.5%. 2nd group One or more selected from Ca: 0.0002-0.05%, Mg: 0.0002-0.012%, Zr: 0.0002-0.012%, and REM: 0.0002-0.05%. Group 3 One or more selected from Pb: 0.0001-0.30%, Se: 0.0001-0.80%, Te: 0.0001-0.30%, Bi: 0.0001-0.50%, S: 0.0001-0.50%, and P: 0.0001-0.30%.

[0008] [4] A stainless steel bar according to any one of [1] to [3], having a crack-free strain rate of 0.1 / s or more at a compression ratio of 70%. [5] A stainless steel bar according to any one of [1] to [4], having a hole depth (tool life) by drilling of 50 mm or more. [6] The stainless steel bar according to any one of [1] to [5], having a coercive force of 5.0 A / m or less.

[0009] [7] An electromagnetic component using the stainless steel bar material according to any one of [1] to [6].

[0010] According to the present invention, it is possible to obtain a stainless steel bar and an electromagnetic part that are excellent in high-speed cold forgeability, machinability, and soft magnetic properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present inventors have conducted various investigations to obtain stainless steel bars and electromagnetic parts that are excellent in high-speed cold forgeability, machinability, and soft magnetic properties, and as a result have discovered the following (a) to (c).

[0012] (a) By combining ferritic stainless steel whose composition is adjusted with one or more of B, Ti, and Nb with the hot rolling process (finish rolling entry temperature, finish rolling roll diameter, heat treatment temperature), it is possible to reduce the average nitride particle size and the amount of dissolved N and B in the steel.

[0013] (b) As a result, in terms of high-speed cold forgeability, the strain rate without cracking at a compression ratio of 70% was 0.1 / s or more, in terms of machinability, the cutting resistance was 50 mm or more, and in terms of soft magnetic properties, the coercive force was 5.0 A / m or less. Thus, a new method was discovered that can improve all of the properties of high-speed cold forgeability, machinability, and soft magnetic properties.

[0014] The present invention has been made based on the above findings. A preferred embodiment of the present invention will be described in detail. In the following description, a preferred embodiment of the present invention will be described as the present invention. Each requirement of the present invention will be described in detail below. In the bar-shaped steel material of the present invention, "bar-shaped steel material" includes "steel bar," "wire rod," "steel wire," "deformed wire," "deformed steel bar," and the like.

[0015] 1. Average particle size of nitride In the steel bar according to the present invention, the average particle diameter of the nitrides is controlled. Specifically, the average particle diameter of the nitrides is set to 10 μm or less. If the average particle diameter of the nitrides exceeds 10 μm, the high-speed cold forgeability is reduced due to coarse nitrides. The average particle diameter of the nitrides is more preferably set to 7 μm or less, and even more preferably set to 5 μm or less. On the other hand, if the average particle diameter of the nitrides is too small, the soft magnetic properties and machinability are deteriorated, so the average particle diameter of the nitrides is preferably 0.01 μm or more. The nitrides include carbonitrides.

[0016] The average particle diameter of the nitrides can be determined by measuring at least one field of view at 400x magnification in the L section of the bar-shaped steel (the section including the center line of the bar-shaped steel) at the surface layer, the center, and the 1 / 4 depth position between the surface layer and the center, identifying the nitrides in the observed fields of view using FE-SEM / ESD, and calculating the average circle equivalent diameter of the nitrides in the same fields of view.

[0017] 2. Amount of dissolved N and B in steel In the steel bar according to the present invention, the amount of solute N in the steel is 0.020% by mass or less, or the amount of solute B in the steel is 0.015% by mass or less, thereby improving the soft magnetic properties and high-speed cold forgeability. Hereinafter, the invention according to the present invention having the preferred composition and the average particle size of the nitrides described above and specifying the amount of solute N in the steel to be 0.020% by mass or less is referred to as "present invention 1." In addition, the invention according to the present invention having the preferred composition and the average particle size of the nitrides described above and specifying the amount of solute B in the steel to be 0.015% by mass or less is referred to as "present invention 2."

[0018] 2-1.Solution N content in steel In the steel bar according to the present invention 1, the amount of solute N in the steel is controlled. Specifically, the amount of solute N in the steel is set to 0.020% by mass or less. If the amount of solute N in the steel exceeds 0.020% by mass, the soft magnetic properties and high-speed cold forgeability are reduced due to lattice distortion caused by the solute N. The amount of solute N in the steel is more preferably set to 0.015% by mass or less, and even more preferably set to 0.01% by mass or less. On the other hand, if the amount of solute N in the steel is too small, the machinability is deteriorated, so the amount of solute N in the steel is preferably set to 0.00001% by mass or more. In addition, in the present invention, 1 In steel, the crystal structure is ferritic steel, so the amount of dissolved N in the steel corresponds to the amount of dissolved N in the ferritic phase.

[0019] The amount of dissolved N in steel was determined by subjecting bar-shaped steel material to electrolytic extraction residue, extracting nitrides, and measuring the amount of N in the nitrides (N pre ) was measured, and the total N content in the steel (N 0 ) and the amount of dissolved N in the steel (=N 0 -N pre ) can be measured.

[0020] 2-2.Solution B content in steel In the steel bar according to the second invention, the problem of the present invention can be solved by controlling the amount of solute B in the steel. Specifically, the amount of solute B in the steel is set to 0.015% by mass or less. This is because if the amount of solute B in the steel exceeds 0.015% by mass, the soft magnetic properties and high-speed cold forgeability decrease due to lattice strain caused by the solute B. The amount of solute B in the steel is more preferably set to 0.010% by mass or less, and even more preferably set to 0.005% by mass or less. On the other hand, if the amount of solute B in the steel is too small, the machinability deteriorates, so the amount of solute B in the steel is preferably set to 0.00001% by mass or more. Note that, in the present invention, 2 In steel, the crystal structure is ferritic steel, so the amount of solute B in the steel corresponds to the amount of solute B in the ferritic phase.

[0021] The amount of dissolved B in steel was determined by subjecting bar-shaped steel material to electrolytic extraction residue, extracting nitrides, and measuring the amount of B in the nitrides (B pre) was measured, and the total B content in the steel (B 0 ) and the amount of dissolved B in steel (=B 0 -B pre ) can be measured.

[0022] 3.Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."

[0023] C: 0.001 to 0.030% C increases the strength and machinability of steel. For this reason, the C content is set to 0.001% or more. However, excessive C content deteriorates the soft magnetic properties, high-speed cold forgeability, and machinability. For this reason, the C content is set to 0.030% or less. The C content is preferably set to 0.020% or less, and more preferably set to 0.015% or less.

[0024] Si: 0.01 to 4.00% Silicon is contained as a deoxidizing element to improve soft magnetic properties and machinability. For this reason, the silicon content is set to 0.01% or more, and preferably 0.10% or more. However, excessive silicon content deteriorates high-speed cold forgeability, soft magnetic properties, and machinability. For this reason, the silicon content is set to 4.00% or less. The silicon content is preferably set to 3.00% or less, and more preferably 1.50% or less.

[0025] Mn: 0.01 to 2.00% Mn improves the strength, soft magnetic properties, and machinability of steel. For this reason, the Mn content is set to 0.01% or more, and preferably 0.05% or more. However, excessive Mn content reduces the soft magnetic properties, high-speed cold forgeability, and machinability. Also, corrosion resistance may be reduced. For this reason, the Mn content is set to 2.00% or less. The Mn content is preferably set to 1.00% or less, and more preferably 0.50% or less.

[0026] Ni: 0.01 to 4.00% Ni improves the toughness, soft magnetic properties, high-speed cold forgeability, and machinability of steel. For this reason, the Ni content is set to 0.01% or more, and preferably 0.05% or more. However, excessive Ni content reduces the soft magnetic properties, high-speed cold forgeability, and machinability. For this reason, the Ni content is set to 4.00% or less. The Ni content is preferably set to 3.00% or less, more preferably 1.00% or less, and even more preferably 0.50% or less.

[0027] Cr: 8.0~35.0% Cr improves corrosion resistance, soft magnetic properties, high-speed cold forgeability, and machinability. For this reason, the Cr content is set to 8.0% or more. The Cr content is preferably set to 10.0% or more. However, excessive Cr content reduces the soft magnetic properties, high-speed cold forgeability, and machinability. The Cr content is set to 35.0% or less. The Cr content is preferably set to 21.0% or less, and more preferably set to 20.0% or less.

[0028] Mo: 0.01 to 5.00% Mo improves corrosion resistance, soft magnetic properties, high-speed cold forgeability, and machinability. For this reason, the Mo content is set to 0.01% or more. However, excessive Mo content reduces high-speed cold forgeability, soft magnetic properties, and machinability. For this reason, the Mo content is set to 5.00% or less. The Mo content is preferably set to 3.00% or less, more preferably set to 2.00% or less, and even more preferably set to 1.50% or less.

[0029] Cu: 0.01-2.00% Cu improves corrosion resistance, soft magnetic properties, high-speed cold forgeability, and machinability. For this reason, the Cu content is set to 0.01% or more, and preferably 0.05% or more. However, excessive Cu content reduces the soft magnetic properties, high-speed cold forgeability, and machinability. For this reason, the Cu content is set to 2.00% or less. The Cu content is preferably set to 1.00% or less, more preferably 0.80% or less, and even more preferably 0.40% or less.

[0030] N: 0.001 to 0.030% N improves the strength and machinability of steel materials. It is also an element that forms nitrides. For this reason, the N content is set to 0.001% or more, and preferably 0.002% or more. However, if N is contained in excess, the soft magnetic properties, machinability, and high-speed cold forgeability are reduced. In addition, the average particle size of the nitrides increases, and the amount of dissolved N increases. For this reason, the N content is set to 0.030% or less. The N content is preferably set to 0.025% or less, and more preferably 0.020% or less.

[0031] Al: 7.000% or less Al has the effect of promoting deoxidation and improving the inclusion cleanliness level. In addition, the addition of Al improves soft magnetic properties, high-speed cold forgeability, and machinability. However, if Al is contained in excess, the effect is saturated, and the soft magnetic properties, high-speed cold forgeability, and machinability are reduced. In addition, toughness is reduced due to coarse inclusions. For this reason, the Al content is set to 7.000% or less. The Al content is preferably set to 3.000% or less, more preferably set to 0.100% or less, and even more preferably set to 0.020% or less. On the other hand, in order to obtain the above effect, the Al content is preferably set to 0.001% or more.

[0032] In addition to the above elements, the steel bar according to the present invention contains one or more elements selected from Ti: 0.001% or more, Nb: 0.001% or more, and B: 0.0001% or more within the composition ranges below. These elements are the main elements that constitute the nitrides, and need to be controlled because they relate to the average particle size of the nitrides and the amount of dissolved N. Of Ti, Nb, and B, elements not selected above may not be contained or may be contained within the composition ranges below.

[0033] Ti: 0 to 2.00% Ti has the effect of increasing the strength, soft magnetic properties, high-speed cold forgeability, and machinability of steel. In addition, Ti forms nitrides and is related to the amount of dissolved N. Furthermore, since it forms carbonitrides, it suppresses the formation of Cr carbides and suppresses the formation of Cr depleted layers. As a result, it has the effect of preventing intergranular corrosion. For this reason, the Ti content is set to 0.001% or more. However, if Ti is contained excessively, the soft magnetic properties, machinability, and high-speed cold forgeability decrease. In addition, the average particle size of the nitrides increases. For this reason, the Ti content is set to 2.00% or less. The Ti content is preferably set to 1.00% or less, more preferably set to 0.50% or less, even more preferably set to 0.50% or less, and even more preferably set to 0.25% or less. In order to exhibit the effect, it is preferable to contain 0.01% or more. 0.05% or more is more preferable. It may be 0.10% or more.

[0034] Nb: 0-2.00% Nb has the effect of increasing the strength, soft magnetic properties, high-speed cold forgeability, and machinability of steel. In addition, Nb forms nitrides and is related to the amount of dissolved N. Furthermore, since it forms carbonitrides, it suppresses the formation of Cr carbides and suppresses the formation of Cr depleted layers. As a result, it has the effect of preventing intergranular corrosion. For this reason, the Nb content is set to 0.001% or more. However, if Nb is contained excessively, the soft magnetic properties, machinability, and high-speed cold forgeability decrease. In addition, the average particle size of the nitrides increases. For this reason, the Nb content is set to 2.00% or less. The Nb content is preferably set to 1.00% or less, more preferably set to 0.80% or less, and even more preferably set to 0.60% or less. In order to exhibit the effect, it is preferable to contain 0.02% or more. It is more preferable to contain 0.05% or more. It may be 0.10% or more.

[0035] B: 0~0.1000% B has the effect of improving the soft magnetic properties, high-speed cold forgeability, and machinability of the steel material. In addition, B forms boron nitrides such as BN, and is related to the amount of dissolved N and the amount of dissolved B. In particular, BN contributes to improving machinability. For this reason, the B content is set to 0.0001% or more. However, if B is contained in excess, the soft magnetic properties, machinability, and high-speed cold forgeability decrease. In addition, the average particle size of the nitride increases. For this reason, the B content is set to 0.1000% or less. The B content is preferably set to 0.0200% or less, and more preferably set to 0.0100% or less. In order to exhibit the effect, it is preferable to contain 0.0005% or more. It is more preferable to contain 0.0010% or more. It may be 0.0020% or more.

[0036] In addition to the above elements, the steel bar according to the present invention may contain, as necessary, one or more elements selected from the group consisting of Sn, V, W, Ga, Co, Sb and Ta as elements of a first group.

[0037] Sn: 0 to 2.50% Sn has the effect of improving corrosion resistance, soft magnetic properties, high-speed cold forgeability, and machinability, so it may be contained as necessary. However, if Sn is contained in excess, the soft magnetic properties, high-speed cold forgeability, and machinability are reduced. In addition, the toughness is reduced due to grain boundary segregation of Sn. For this reason, the Sn content is set to 2.50% or less. The Sn content is more preferably set to 1.00% or less, and even more preferably set to 0.20% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably set to 0.0001% or more, and more preferably set to 0.05% or more.

[0038] V: 0~2.0% V has the effect of improving soft magnetic properties, high-speed cold forgeability, and machinability, so it may be contained as necessary. However, if V is contained in excess, the soft magnetic properties, high-speed cold forgeability, and machinability are reduced. In addition, the toughness is reduced due to coarse carbonitrides. For this reason, the V content is set to 2.0% or less. The V content is preferably set to 1.0% or less, more preferably set to 0.5% or less, and even more preferably set to 0.1% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.001% or more.

[0039] W:0~3.00% W has the effect of improving corrosion resistance, so it may be contained as necessary. However, if W is contained in excess, soft magnetic properties, high-speed cold forgeability, and machinability are reduced. In addition, toughness is reduced due to coarse carbonitrides. For this reason, the W content is set to 3.00% or less. The W content is preferably set to 2.00% or less, and more preferably set to 1.50% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.05% or more, and more preferably set to 0.10% or more.

[0040] Ga: 0 to 0.05% Ga has the effect of improving corrosion resistance, so it may be contained as necessary. However, if Ga is contained in excess, hot workability decreases. For this reason, the Ga content is set to 0.05% or less. On the other hand, in order to obtain the above effect, the Ga content is preferably set to 0.0004% or more.

[0041] Co: 0 to 2.50% Co has the effect of improving the strength, soft magnetic properties, high-speed cold forgeability, and machinability of the steel material, so it may be contained as necessary. In addition, the addition of an appropriate amount of Co increases the saturation magnetic flux density, thereby improving the soft magnetic properties. However, if Co is contained in excess, the soft magnetic properties, high-speed cold forgeability, and machinability decrease. For this reason, the Co content is set to 2.50% or less. The Co content is preferably set to 1.00% or less, and more preferably set to 0.80% or less. On the other hand, in order to obtain the above effect, the Co content is preferably set to 0.05% or more, and more preferably set to 0.10% or more.

[0042] Sb: 0 to 2.50% Sb has the effect of improving corrosion resistance, so it may be contained as necessary. However, if Sb is contained in excess, soft magnetic properties, high-speed cold forgeability, and machinability are reduced. For this reason, the Sb content is set to 2.50% or less. The Sb content is more preferably set to 1.00% or less, and even more preferably set to 0.20% or less. On the other hand, in order to obtain the above effect, the Sb content is preferably set to 0.01% or more, and more preferably set to 0.05% or more.

[0043] Ta: 0 to 2.50% Ta has the effect of improving corrosion resistance, so it may be contained as necessary. However, if Ta is contained in excess, the soft magnetic properties, high-speed cold forgeability, and machinability are reduced. For this reason, the Ta content is set to 2.50% or less. The Ta content is preferably set to 1.50% or less, and more preferably set to 0.90% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably set to 0.01% or more, more preferably set to 0.04% or more, and even more preferably set to 0.08% or more.

[0044] In addition to the above elements, the steel bar according to the present invention may contain, as necessary, one or more elements selected from Ca, Mg, Zr, and REM as elements of a second group. Ca: 0 to 0.05% Magnesium: 0 to 0.012% Zr: 0 to 0.012% REM: 0~0.05% Ca, Mg, Zr, and REM may be contained as necessary for deoxidization. However, excessive content of each of these elements reduces soft magnetic properties, high-speed cold forgeability, and machinability. In addition, toughness is reduced due to coarse inclusions. For this reason, the Ca content is set to 0.05% or less, Mg content is set to 0.012% or less, Zr content is set to 0.012% or less, and REM content is set to 0.05% or less. The Ca content is preferably set to 0.010% or less, and more preferably set to 0.005% or less. The Mg content is preferably set to 0.010% or less, and more preferably set to 0.005% or less. The Zr content is preferably set to 0.010% or less, and more preferably set to 0.005% or less. The REM content is preferably set to 0.010% or less. On the other hand, in order to obtain the above effects, it is preferable that the Ca content is 0.0002% or more, the Mg content is 0.0002% or more, the Zr content is 0.0002% or more, and the REM content is 0.0002% or more. The Ca content is more preferably 0.0004% or more, and further preferably 0.001% or more. The Mg content is preferably 0.0004% or more. twist The Zr content is preferably 0.0004% or more, and more preferably 0.001% or more. The REM content is preferably 0.0004% or more, and more preferably 0.001% or more. REM is a collective term for 17 elements, including 15 lanthanoid elements, Y, and Sc. One or more of these 17 elements can be contained in steel, and the REM content refers to the total content of these elements.

[0045] In addition to the above elements, the steel bar according to the present invention may contain one or more elements selected from Pb, Se, Te, Bi, S and P as elements of a third group, if necessary. Pb: 0~0.30%, Se: 0-0.80%, Te: 0-0.30%, Bi: 0 to 0.50%, S: 0~0.50%, P: 0-0.30%, Pb, Se, Te, Bi, S and P may be added as necessary for machinability. However, excessive addition of these elements reduces the soft magnetic properties and high-speed cold forgeability. In addition, toughness also decreases. For this reason, the following is set: Pb: 0.30% or less, Se: 0.80% or less, Te: 0.30% or less, Bi: 0.50% or less, S: 0.50% or less. % Below, P:0.30 % The content of Pb is preferably 0.1% or less, and more preferably 0.05% or less. The content of Se is preferably 0.1% or less, and more preferably 0.05% or less. The content of Te is preferably 0.1% or less, and more preferably 0.05% or less. The content of Bi is preferably 0.1% or less, and more preferably 0.05% or less. The content of S is preferably 0.1% or less, and more preferably 0.05% or less. The content of P is preferably 0.1% or less, and more preferably 0.05% or less. On the other hand, in order to obtain the above effects, it is preferable that Pb: 0.0001% or more, Se: 0.0001% or more, Te: 0.0001% or more, Bi: 0.0001% or more, S: 0.0001% or more, and P: 0.0001% or more. The Pb content is more preferably 0.0004% or more, and even more preferably 0.001% or more. The Se content is more preferably 0.0004% or more, and even more preferably 0.001% or more. The Te content is more preferably 0.0004% or more, and even more preferably 0.001% or more. The Bi content is more preferably 0.0004% or more, and even more preferably 0.001% or more. The S content is more preferably 0.0001% or more, and even more preferably 0.0002% or more. The P content is more preferably 0.0004% or more, and further preferably 0.001% or more.

[0046] The steel of the present invention Material In the chemical composition of the steel, the balance is Fe and impurities. MaterialThe term "common components" refers to components that are mixed in during industrial production of the above-mentioned compound due to various factors in the manufacturing process, such as raw materials such as ores and scraps, and that are acceptable within a range that does not adversely affect the present invention.

[0047] Examples of impurities include O, Zn, and H. It is preferable to reduce impurities, but if impurities are contained, it is desirable for the amount of O, Zn, and H to be 0.01% or less.

[0048] 4. Manufacturing method A preferred method for producing the electromagnetic stainless steel (stainless steel bar) according to the present invention will be described. The stainless steel bar according to the present invention can obtain the effects described above regardless of the production method, but the stainless steel bar according to the present invention can be stably obtained by, for example, the following production method.

[0049] In the stainless steel bar of the present invention, a steel having the above-mentioned chemical composition is melted, a slab having a predetermined diameter is cast, and then hot or warm bar rolling is performed by rough rolling, intermediate rolling, and finish rolling, and the bar is heat-treated. It is preferable to perform tilt rolling before rough rolling. Then, pickling or the like is appropriately performed as necessary.

[0050] 4-1. Finish rolling entry temperature In the hot rolling of the bar-shaped steel material, it is preferable to control the entry temperature of the finish rolling. The entry temperature of the finish rolling of the bar-shaped steel material changes the average particle size of the nitrides and also changes the solid solution fraction of N and B contained in the steel. Therefore, the entry temperature of the finish rolling affects the soft magnetic properties, high-speed cold forgeability, and machinability. If the entry temperature of the finish rolling of the bar-shaped steel material is set to more than 1200°C, the nitrides become more easily dissolved, and the amount of solid solution N and the amount of solid solution B increase. As a result, the soft magnetic properties and high-speed cold forgeability decrease. In addition, the average particle size of the nitrides becomes too small, so the machinability decreases. Therefore, the entry temperature of the finish rolling is set to 1200°C or less, preferably 1100°C or less, and more preferably 1050°C or less. On the other hand, if the entry temperature of the finish rolling is less than 600°C, the amount of solid solution N becomes too small, so the machinability decreases. In addition, the presence of undissolved nitrides increases the average particle size of the nitrides, which reduces the high-speed cold forgeability. Therefore, the finish rolling entry temperature is set to 600°C or higher. The finish rolling entry temperature is preferably 700°C or higher, and more preferably 800°C or higher.

[0051] 4-2. Roll diameter for finishing rolling The roll diameter of the finish rolling affects the strain distribution and amount of the bar-shaped steel material, and is related to the average particle size of the nitrides and the amount of solute N in the steel, and affects the soft magnetic properties, high-speed cold forgeability, and machinability, so it is necessary to control it. If the finish rolling roll diameter is less than 50 mm, strain is not introduced into the center of the bar-shaped steel material, the formation of fine nitrides on dislocations is not promoted, and the average particle size of the nitrides becomes large. In addition, the amount of solute N increases. As a result, the soft magnetic properties and high-speed cold forgeability decrease. The effect of the finish rolling roll diameter on the amount of solute N in the steel is the same in the case of solute B, and if the finish rolling roll diameter is less than 50 mm, the amount of solute B increases. For this reason, the finish rolling roll diameter is set to 50 mm or more, preferably 80 mm or more, and more preferably 100 mm or more. On the other hand, if the finishing roll diameter exceeds 500 mm, the nitrides become too fine, and the amount of dissolved N and B increases, resulting in poor machinability. Soft Since the magnetic properties are deteriorated, the thickness is set to 500 mm or less, preferably 400 mm or less, and more preferably 300 mm or less.

[0052] 4-3.Heat treatment temperature for bar steel The hot-rolled steel bar is preferably heat-treated. The heat treatment temperature of the steel bar changes the average particle size of the nitrides and the solid solution fraction in the steel. Therefore, the heat treatment temperature of the steel bar affects the soft magnetic properties, high-speed cold forgeability, and machinability. If the heat treatment temperature of the steel bar is more than 1300°C, the nitrides are more likely to dissolve, and the amount of dissolved N and the amount of dissolved B increases. As a result, the soft magnetic properties and high-speed cold forgeability decrease. In addition, the average particle size of the nitrides becomes too small, so the machinability decreases. Therefore, the heat treatment temperature is set to 1300°C or less, preferably 1200°C or less, and more preferably 1100°C or less. On the other hand, if the heat treatment temperature of the steel bar is less than 500°C, the amount of dissolved N becomes too small, so the machinability decreases. In addition, the presence of undissolved nitrides increases the average particle size of the nitrides, so the high-speed cold forgeability decreases. Therefore, the heat treatment temperature is set to 500°C or more. The heat treatment temperature is preferably 600°C or higher, and more preferably 700°C or higher.

[0053] 5. Quality of Stainless Steel Bars The stainless steel bar of the present invention has a crack-free strain rate of 0.1 / s or more at a compression ratio of 70%, and can achieve excellent high-speed cold forgeability. The stainless steel bar of the present invention can achieve a hole depth (tool life) of 50 mm or more when drilled, and can achieve excellent machinability. The stainless steel bar of the present invention has a coercive force of 5.0 A / m or less, and can achieve excellent soft magnetic properties.

[0054] 6.Electromagnetic components Electromagnetic parts using the stainless steel bar of the present invention are, for example, cores and connectors for injectors and solenoid valves, and because the bar steel material has excellent soft magnetic properties, it can achieve effects such as "improved magnetic attraction force," "reduced diameter of parts," and "improved responsiveness." In addition, because the bar steel material has excellent high-speed cold forgeability and machinability, it is possible to manufacture the parts with high productivity and low cost, and it is also possible to achieve near-net shape by cold forging.

[0055] The present invention will be described in more detail below with reference to examples. However, the present invention is merely illustrative and is not limited to these examples. EXAMPLES

[0056] Steels having the chemical compositions shown in Tables 1 and 2 were produced. The steels were melted in a 100 kg vacuum melting furnace, assuming AOD production, which is an inexpensive process for producing stainless steel, and cast into slabs with a diameter of 180 mm. The steels were then produced into stainless steel wire rods with a diameter of 20.0 mm under the following manufacturing conditions.

[0057] The conditions are as follows. Specifically, the cast slab is heated, tilt-rolled, rough-rolled, intermediate-rolled, and then finish-rolled under the conditions of No. 123 in Table 6. entrance side Finish rolling was performed at a temperature of 1180°C with a finish rolling roll diameter of 480 mm, and then heat treatment was performed at a temperature of 1290°C under condition No. 123 in Table 6 to produce a wire rod (steel rod) with a diameter of 20.0 mm.

[0058] [Table 1]

[0059] [Table 2]

[0060] The obtained wire rods (steel rods) were evaluated for the average particle size of nitrides, the amount of solute N in the steel, the amount of solute B in the steel, high-speed cold forgeability, soft magnetic properties, and machinability. The results are summarized in Tables 3, 4, and 5 below. Tables 3 and 4 show examples of the present invention and comparative examples corresponding to present invention 1, and the amount of solute N in the steel is shown in the tables. Table 5 shows examples of the present invention and comparative examples corresponding to present invention 2, and the actual amount of solute B in the steel is shown in the table. These measurements were performed according to the following procedure.

[0061] [Table 3]

[0062] [Table 4]

[0063] [Table 5]

[0064] The average particle diameter of the nitrides was measured in one or more visual fields at a magnification of 400x in the L cross section (cross section including the center line of the steel bar) of the steel bar, at the surface layer, the center, and the 1 / 4 depth position between the surface layer and the center. The nitrides in the observed visual fields were identified using FE-SEM / ESD, and the average circle equivalent diameter of the nitrides in the same visual field was calculated. If the average particle diameter of the nitrides was 0.01 to 5 μm, it was rated as "A", if it was 5 to 7 μm, it was rated as "B", if it was 7 to 10 μm, it was rated as "C", and if it was over 10 μm, it was rated as "D". The rods of the present invention Condition When steel materials were used, the results were "A", "B" and "C", and the average particle size of the nitrides was excellent. Note that the nitrides include carbonitrides.

[0065] The amount of dissolved N in steel was determined by subjecting bar-shaped steel material to electrolytic extraction residue, extracting nitrides, and measuring the amount of N in the nitrides (N pre ) was measured, and the total N content in the steel (N 0 ) and the amount of dissolved N in the steel (=N 0 -N pre If the amount of solute N in the steel was 0.00001 to 0.01 mass%, it was rated as "A", if it was 0.01 to 0.015 mass%, it was rated as "B", if it was 0.015 to 0.020 mass%, it was rated as "C", and if it was more than 0.020 mass%, it was rated as "D". Condition When steel materials were used, as shown in Table 3, the results were "A", "B" and "C", and the amount of dissolved N in the steel was excellent.

[0066] The amount of dissolved B in steel was determined by subjecting bar-shaped steel material to electrolytic extraction residue, extracting nitrides, and measuring the amount of B in the nitrides (B pre ) was measured, and the total B content in the steel (B 0 ) and the amount of dissolved B in steel (=B0 -B pre If the amount of solute B in the steel was 0.01 mass% or less, it was rated as "B", if it was 0.01 to 0.015 mass%, it was rated as "C", and if it was more than 0.015 mass%, it was rated as "D". Condition When steel materials were used, as shown in Table 5, the results were "B" and "C," and the amount of dissolved B in the steel was excellent.

[0067] The high-speed cold forgeability was judged from the presence or absence of cracks on the end surface by a compression test. A test piece of φ10×15 mm was prepared, and the test piece was compressed at room temperature with a compression ratio of 70% while changing the strain rate. After the test, the side surface of the test piece was observed and the presence or absence of cracks was judged to evaluate the high-speed cold forgeability. If the strain rate was 10 / s or more without cracks at a compression ratio of 70%, it was rated as "A", if it was 1 / s or more, it was rated as "B", if it was 0.1 / s or more, it was rated as "C", and if it was less than 0.1 / s, it was rated as "D". The rod of the present invention Condition When steel materials were used, the results were "A", "B" and "C", and they had excellent high-speed cold forgeability.

[0068] The soft magnetic properties were measured by coercive force (A / m). Ring-shaped test pieces with a thickness of 3 mm, an outer diameter of 10 mm, and an inner diameter of 8 mm were prepared and subjected to a heat treatment at 950°C for 2 hours, after which the coercive force was measured. If the coercive force was 2.0 A / m or less, it was rated as "A", if it was 3.5 A / m or less, it was rated as "B", if it was 5.0 A / m or less, it was rated as "C", and if it was more than 5.0 A / m, it was rated as "D". Condition When steel was used, the results were "A", "B" and "C", and the soft magnetic properties were excellent.

[0069] The machinability was evaluated based on the tool life. A test piece of φ15×30 mm was prepared and drilled in the longitudinal direction (dry type, drill diameter: φ4 mm, cutting speed: 25 m / min, feed: 0.1 mm / rev, tool: SKH9). The hole depth at which cutting was impossible was measured and the machinability was evaluated. If the hole depth (tool life) was 130 mm or more, it was rated as "A", if it was 100 mm or more, it was rated as "B", if it was 50 mm or more, it was rated as "C", and if it was less than 50 mm, it was rated as "D". Condition When steel was used, the results were "A", "B" and "C", showing excellent machinability. EXAMPLES

[0070] Next, steel type P shown in Table 1 was used to prepare a steel bar having a diameter of 15 mm under the conditions shown in Tables 6 and 7. The history other than the finish rolling entry temperature, finish rolling roll diameter, and heat treatment temperature was the same as in Example 1. The average particle size of nitrides, the amount of solute N in the steel, the amount of solute B in the steel, high-speed cold forgeability, soft magnetic properties, and machinability of the prepared wire rod (steel bar) were measured by the above-mentioned methods. The results are summarized in Tables 6 and 7. Table 6 shows examples of the present invention and comparative examples corresponding to present invention 1, and the amount of solute N in the steel is shown in the table. Table 7 shows examples of the present invention and comparative examples corresponding to present invention 2, and the actual amount of solute B in the steel is shown in the table.

[0071] [Table 6]

[0072] [Table 7] [Industrial Applicability]

[0073] According to the present invention, High speed cold forgeability, machinability, and It is possible to obtain a steel bar having excellent soft magnetic properties, which is extremely useful in industry.

Claims

1. The chemical composition, in mass%, is C: 0.001-0.030%, Si: 0.01-4.00%, Mn: 0.01 to 2.00%, Ni: 0.01 to 4.00%, Cr: 8.0-35.0%, Mo: 0.01-5.00%, Cu: 0.01-2.00%, N: 0.001-0.030%, Al: 7.000% or less; moreover, Ti: 0-2.00%, Nb: 0 to 2.00%, B: 0 to 0.1000%; Contains one or more selected from Ti: 0.001% or more, Nb: 0.001% or more, and B: 0.0001% or more; Sn: 0 to 2.50%, V: 0 to 2.0%, W: 0-3.00%, Ga: 0-0.05%, Co: 0 to 2.50%, Sb: 0 to 2.50%, Ta: 0-2.50%, Ca: 0-0.05%, Mg: 0 to 0.012%, Zr: 0 to 0.012%, REM: 0-0.05%, Pb: 0 to 0.30%, Se: 0-0.80%, Te: 0 to 0.30%, Bi: 0 to 0.50%, S: 0-0.50%, P: 0 to 0.30%; The balance is Fe and impurities. The average particle size of the nitride is 0.01 μm or more and 10 μm or less, the amount of solute N in the steel is 0.020 mass% or less and / or the amount of solute B in the steel is 0.015 mass% or less, A stainless steel bar having a compression ratio of 70% and a strain rate without cracking of 0.1 / s or more, or a hole depth (tool life) when drilled of 50 mm or more, or a coercive force of 5.0 A / m or less.

2. The stainless steel bar according to claim 1, wherein the chemical composition further contains, in mass%, one or more elements selected from the following first to third groups. 1st group Sn: 0.0001 to 2.5%, V:0.001~2.0% W: 0.05-3.0%, Ga: 0.0004-0.05%, Co: 0.05-2.5%, Sb: 0.01 to 2.5%, and Ta: 0.01-2.5%, One or more selected from the above. 2nd group Ca: 0.0002-0.05%, Mg: 0.0002-0.012%, Zr: 0.0002 to 0.012%, and REM: 0.0002-0.05%, One or more selected from the above. 3rd group Pb: 0.0001 to 0.30%, Se: 0.0001-0.80%, Te: 0.0001 to 0.30%, Bi: 0.0001 to 0.50%, S: 0.0001-0.50%, P: 0.0001-0.30%, One or more selected from the above.

3. 3. An electromagnetic part using the stainless steel bar material according to claim 1 or 2.

Citation Information

Patent Citations

  • Free-cutting, corrosion resistant and soft magnetic steel for bar or pipe with superior toughness

    JP1984232258A

  • Stainless steel excellent in corrosion resistance

    JP1991044448A

  • Magnetic stainless steel

    JP1994049605A

  • Magnetic stainless steel

    JP1994049606A

  • Electromagnetic stainless steel excellent in cold forgeability

    JP2000160302A